Digital Kampanye Zero Waste Indonesia - Shafira Fauzani; Maman Chatamallah (UNISBA Press, 2022)
Abstract. Humans are an important element in protecting the environment, because the symbiotic mutualism of which must continue to go along with the development of the earth and technology. However, there are still many people who do not respect their environment to always live in harmony, because the amount of waste and waste produced by humans is increasing every day, thus environmental problems, especially waste problems in Indonesia, are increasing in number. Zero Waste Indonesia as an online-based community that aims to change the lifestyle of the Indonesian people. In the 30 Days Zero Waste Challenge program, Zero Waste Indonesia campaigns for a minimal waste style to reduce the amount of waste in Indonesia. In this research on the digital program of the 30 Days Zero Waste Challenge campaign, qualitative research methods are used with a case study approach. Researchers used data collection techniques, namely interviews, documentation, and literature study. The purpose of this study is to find out how to plan, how to implement, why the program was chosen to be campaigned on Instagram and to find out how the supporting factors and digital barriers for the 30 Days Zero Waste Challenge campaign on Instagram @zerwowaste.id_official. The subject of this research with the main informant is Zero Waste Indonesia who can indeed provide information and with the support of informants it is hoped that they can provide views from different perspectives or information about the digital program of the 30 Days Zero Waste Challenge campaign and about waste problems in Indonesia. Abstrak. Manusia merupakan unsur yang penting dalam menjaga lingkungannya, karena simbiosis mutualisme diantaranya harus terus berjalan seiring berkembangnya bumi dan teknologi. Tetapi masih banyaknya manusia yang tidak menghalukan lingkungannya untuk selalu hidup selaras, karena jumlah sampah dan limbah yang dihasilkan manusia selalu meningkat setiap harinya, dengan begitu permasalahan lingkungan terutama permasalahan sampah di Indonesia jumlahnya semakin meningkat. Zero Waste Indonesia sebagai salah satu komunitas berbasis online yang bertujuan dalam mengubah gaya hidup masyarakat Indonesia. Dalam program 30 Days Zero Waste Challenge, Zero Waste Indonesia mengkampanyekan gaya minim sampah untuk mengurangi jumlah sampah di Indonesia. Pada penelitian mengenai program digital kampanye 30 Days Zero Waste Challenge ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Peneliti menggunakan teknik pengumpulan data yaitu wawancara, dokumentasi, dan studi kepustakaan. Tujuan dari penelitian ini yakni untuk mengetahui bagaimana perencanaan, bagaimana pelaksanaan, mengapa program tersebut dipilih untuk dikampanyekan di Instagram dan mengatahui bagaimana faktor pendukung dan hambatan digital kampanye 30 Days Zero Waste Challenge pada Instagram @zerwowaste.id_official. Subjek penelitian ini dengan informan utama ialah pihak Zero Waste Indonesia yang memang dapat memberikan informasi dan dengan adanya informan pendukung diharapkan dapat memberikan pandangan dari sudut pandang yang berbeda atau informasi mengenai program digital kampanye 30 Days Zero Waste Challenge serta mengenai permasalahan sampah yang ada di Indonesia.